Interleukins in diagnosis of perinatal asphyxia: A systematic review - Boskabadi, Hassan (Int J Reprod Biomed, 2019)
BACKGROUND: Biochemical markers including interleukins (ILs) has been proposed for early diagnosis of asphyxia OBJECTIVE: This study has aimed to systematically review the significance of IL measurements in the diagnosis of perinatal asphyxia. MATERIALS AND METHODS: PubMed, Cochrane Library, Web of Science, Embase, and Scopus databases before 2017 were searched for the following keywords: asphyxia, neonatal, interleukin, and diagnosis. A total of 13 out of 300 searched papers were finally selected for evaluation. Interleukins under study were IL6 and interleukin 1 [Formula: see text] (IL-1 [Formula: see text]). Interleukins had been measured in 10 studies by serum samples, 2 studies by samples of Cerebro Spinal Fluid (CSF), and 1 study by sample of umbilical cord blood. The inclusion criteria were: studies on neonates, with adequate information from the test results and studies using markers other than ILs to detect asphyxia; however, studies with only abstracts available were excluded. RESULTS: Research on the issue suggests that IL6 > 41 Pg/dl has the sensitivity of 84.88% and the specificity of 85.43%, whereas IL-1 [Formula: see text] > 4.7 Pg/dl has the sensitivity of 78% and specificity of 83% in the diagnosis of neonatal asphyxia. Among diagnostic ILs for neonatal asphyxia, combination of IL6 and IL-1 [Formula: see text] had the highest sensitivity, that is, 92.9%. CONCLUSION: IL6 and IL-1 [Formula: see text] of serum samples were used in the early diagnosis of perinatal asphyxia and are useful predictors for the outcomes of perinatal asphyxia and its intensity. In addition, simultaneous evaluation of IL-1 [Formula: see text] and IL6 can improve the sensitivity of the early diagnosis of perinatal asphyxia.